Nostalgia digital: Fortaleza em fotografias do século XX - Almeida, Marcos Roberto Moura de (2024)
This study explores the phenomenon of sharing old photographs in virtual communities, focusing on the Fortaleza Antiga Facebook group, where members exchange photos and memories of Fortaleza, Ceará. The research examines the relationship between these images and the evocation of nostalgia among users. Employing a theoretical framework that encompasses photography, nostalgia, and social networks, the study investigates how photography serves as a link between past and present, invoking feelings and memories. Theoretical insights from Roland Barthes (1984) and Georges Didi-Huberman (2012) describe photography as a human fragment that transcends time and has the power to provoke observers. The evolution of the concept of nostalgia is analyzed from its origins as a medical condition to its contemporary commercial and cultural significance, referencing Katharina Niemeyer (2018), Maurice Halbwacks (1990), and Svetlana Boym (2017). Additionally, the study delves into theories of virtual communities and social networks, with perspectives from Raquel Recuero (2005, 2009), Manuel Castells (1999), and Clay Shirky (2011), to understand how these platforms facilitate nostalgic sharing. The methodology employed is Thematic Analysis, as proposed by Braun and Clark (2006), applied to a sample of 20 posts from the group, specifically focusing on nostalgia. The research aims to elucidate how interactions and the expression of feelings towards old images contribute to a deeper understanding of memory and nostalgia dynamics in virtual communities.